Ultrafast excited-state dynamics of 2, 4-dimethylpyrrole. Issue 43 (30th October 2017) - Yang, Dongyuan; Chen, Zhichao; He, Zhigang; Wang, Hengding; Min, Yanjun; Yuan, Kaijun; Dai, Dongxu; Wu, Guorong; Yang, Xueming
Abstract : Ultrafast excited-state dynamics of 2, 4-dimethylpyrrole are studied in detail following deep UV excitation. Abstract : The ultrafast excited-state dynamics of 2, 4-dimethylpyrrole following excitation at wavelengths in the range of 255.8–199.7 nm are studied using the time-resolved photoelectron imaging method. It is found that excitation at longer wavelengths (255.8, 250.0, 246.0 and 242.0 nm) results in population of the S1 ( 1 πσ*) state, which decays out of the photoionization window in less than 30 fs. At 237.7 nm, the second 1 πσ* state is excited, which decays in about 130 fs. At shorter pump wavelengths (231.8, 224.8, 217.5 and 199.7 nm), the assignments are less clear-cut. We tentatively assign the initially photoexcited states to the 1 π3p Rydberg states, which decay in about 60 fs, with internal conversion to the S1 ( 1 πσ*) state as one of the decay channels. The lifetimes of these 1 π3p Rydberg states vary little with the pump wavelengths in this wavelength range.